2016
DOI: 10.1007/s11356-016-7660-7
|View full text |Cite
|
Sign up to set email alerts
|

Baseline seasonal investigation of nutrients and trace metals in surface waters and sediments along the Saigon River basin impacted by the megacity of Ho Chi Minh (Vietnam)

Abstract: The Saigon River, Southern Vietnam, crosses one of the most dynamic developing Megacity in Southeast Asia: Ho Chi Minh City (HCMC). The increased economic, industrial, and domestic developments may affect the environmental quality of water and halieutic resources. In this study, we evaluated the seasonal (dry and wet seasons) biogeochemical state of the Saigon River during two snapshot campaigns conducted along the river basin upstream from HCMC; the Saigon River was characterized by slightly acidic (pH 5.7-7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 62 publications
12
48
0
Order By: Relevance
“…The POCSED content ranges from 0.2 to 1.5% (Table 6). MetalSED concentrations measured in the Tien River (Table 6) are in the same range as previously observed in this system (Cenci and Martin, 2004;Noh et al, 2013) and are in the low concentration range of the main Asian Rivers (Table 4) such as the Yangtze River Estuary (Wang et al, 2015), the Huanghe River Estuary (Wang et al, 2017), the Pearl River Estuary (Zhang et al, 2013), the Ganges-Brahmaputra Rivers (Datta and Subramanian, 1998) and including the Saigon River (Strady et al, 2017). Cenci and Martin (2 0 04) observed that MetalSED in the Mekong Delta varies spatially but not seasonally.…”
Section: Factors Controlling Metal Distributions In the Tien River Susupporting
confidence: 81%
See 4 more Smart Citations
“…The POCSED content ranges from 0.2 to 1.5% (Table 6). MetalSED concentrations measured in the Tien River (Table 6) are in the same range as previously observed in this system (Cenci and Martin, 2004;Noh et al, 2013) and are in the low concentration range of the main Asian Rivers (Table 4) such as the Yangtze River Estuary (Wang et al, 2015), the Huanghe River Estuary (Wang et al, 2017), the Pearl River Estuary (Zhang et al, 2013), the Ganges-Brahmaputra Rivers (Datta and Subramanian, 1998) and including the Saigon River (Strady et al, 2017). Cenci and Martin (2 0 04) observed that MetalSED in the Mekong Delta varies spatially but not seasonally.…”
Section: Factors Controlling Metal Distributions In the Tien River Susupporting
confidence: 81%
“…3) suggesting intense desorption processes from particles occurring in the salinity gradient. This bell-shaped pattern is well documented for CdF as a chloride-induced desorption from the suspended sediments and has been previously observed in the Mekong Delta (Cenci and Martin, 20 04 ) and other estuaries like the Gironde Estuary (Kraepiel et al, 1997;Dabrin et al, 2009), the Pearl River (Wang et al, 2012a), the Saigon River (Strady et al, 2017) and the Huanghe River Estuary (Wang et al, 2016b). For CuF, even if a conservative behaviour is more usual and has been observed in the Mekong Delta (e.g.…”
Section: Filtered and Suspended Particulate Metal Dynamics In The Tiesupporting
confidence: 73%
See 3 more Smart Citations